2014
DOI: 10.15171/ijhpm.2014.129
|View full text |Cite
|
Sign up to set email alerts
|

Have health human resources become more equal between rural and urban areas after the new reform?

Abstract: The lack of health human resources is a global issue. China also faces the same issue, in addition to the equity of human resources allocation. With the launch of new healthcare reform of China in 2009, have the issues been improved? Relevant data from China Health Statistical Yearbook and a qualitative study show that the unequal allocation of health human resources is getting worse than before.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 8 publications
(6 reference statements)
2
22
0
1
Order By: Relevance
“…Therefore, it is of utmost importance that equity in the allocation of health professionals is improved in the country. By studying the changes of health professionals in rural and urban areas, Qian Yang and Hengjin Dong's editorial on December 2014 is interesting and valuable because it addresses an important topic in health policy research and discusses the effects of China's most recent healthcare reforms on rural health workforce (8). In China, distribution of health professionals is largely determined by the market instead of the government because health professionals have the right to practice wherever they choose based on their own preferences and the availability of positions.…”
mentioning
confidence: 99%
“…Therefore, it is of utmost importance that equity in the allocation of health professionals is improved in the country. By studying the changes of health professionals in rural and urban areas, Qian Yang and Hengjin Dong's editorial on December 2014 is interesting and valuable because it addresses an important topic in health policy research and discusses the effects of China's most recent healthcare reforms on rural health workforce (8). In China, distribution of health professionals is largely determined by the market instead of the government because health professionals have the right to practice wherever they choose based on their own preferences and the availability of positions.…”
mentioning
confidence: 99%
“…Finally, the unenthusiastic attitude of primary care workers might be due to their feeling unprepared for the referral. In our previous study, people considered the level of medical skill of the current primary health workforce to be the biggest obstacle to referral implementation (Yang & Dong, 2014). The current study provides another possible interpretation for the policy implementation difficulties.…”
Section: Discussionmentioning
confidence: 73%
“…Our qualitative study of a province in eastern China in 2013 also revealed that both large and public township hospitals were still overcrowded (Yang & Dong, 2014). Thus, it is likely that the structure of health services allocation, which is in the shape of an inverted triangle, with large hospitals at the top, is the underlying problem.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…These countries have a low density of physicians and a high burden of disease, worsening health inequities . Nations with large populations and economic growth in recent decades, such as China, Brazil and India, have difficulties in meeting the growing health needs of their populations and have a shortage of professionals . Even countries with well‐established health systems have regions with a lower number of physicians and these deficits may be addressed by doctors trained in other countries .…”
Section: Introductionmentioning
confidence: 99%